THE INFLUENCE OF INSTITUTIONAL OWNERSHIP ON CORPORATE VALUES WITH DEBT EQUITY RATIO AND PROFITABILITY AS INTERVENING VARIABLES - Syifa Alifia; Fauji Sanusi (Universitas Muhammadiyah Malang, 2021)
This study aims to Determine the Effect of Institutional Ownership (INST) on Corporate Valuesproxied by Tobin's Q with Debt Equity Ratio (DER) and Profitability as proxied by Return on Assets (ROA) as intervening variables in the mining sector companies in the 2011-2017 period. The number of samples in this study is 6 companies, with a purposive sampling method. The data analysis technique in this study is multiple linear regression. The results of this study state that (1) Institutional Ownership does not effect on Tobins'Q; (2) Institutional Ownership does not affect Debt Equity Ratio; (3) Debt Equity Ratio does not effect on Tobins'Q; (4) Institutional Ownership has a significant positive effect on Return on Assets; (5) Return on Assets has a significant positive effect on Tobin's Q. (6) The Debt Equity Ratio is not able to mediate the relationship between Institutional Ownership of Tobin's Q; and (7) Return on Assets can mediate the relationship between Institutional Ownership of Tobin's Q but is not significant.